2021
DOI: 10.1111/nph.17404
|View full text |Cite|
|
Sign up to set email alerts
|

Climate and functional traits jointly mediate tree water‐use strategies

Abstract: Tree water use is central to plant function and ecosystem fluxes. However, it is still unknown how organ-level water-relations traits are coordinated to determine whole-tree water-use strategies in response to drought, and whether this coordination depends on climate.Here we used a global sap flow database (SAPFLUXNET) to study the response of water use, in terms of whole-tree canopy conductance (G), to vapour pressure deficit (VPD) and to soil water content (SWC) for 142 tree species. We investigated the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 92 publications
2
59
0
Order By: Relevance
“…Climate change will pose higher pressure on forests through increasing temperatures and higher frequency and intensity of droughts, exerting higher drought limitations on growth whilst reducing low‐temperature limitations (Babst et al, 2019; Pompa‐Gárcia et al, 2021). Such changes may influence species distributions, promoting retractions and drought‐induced mortality at dry edges (Anderegg et al, 2019) and growth—temperature decoupling and expansion at cold treelines (Camarero et al, 2021), with potential influences on carbon stocks and ecosystem fluxes (Eller et al, 2020; Flo et al, 2021; Martin et al, 2018; Sabot et al, 2019). Our results indicating that cross‐species interannual growth variability associated with drought is related to WD and hydraulic traits support the importance of such traits on regulating carbon fluxes, which is particularly relevant under the expected increase of drought pressures on forests.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change will pose higher pressure on forests through increasing temperatures and higher frequency and intensity of droughts, exerting higher drought limitations on growth whilst reducing low‐temperature limitations (Babst et al, 2019; Pompa‐Gárcia et al, 2021). Such changes may influence species distributions, promoting retractions and drought‐induced mortality at dry edges (Anderegg et al, 2019) and growth—temperature decoupling and expansion at cold treelines (Camarero et al, 2021), with potential influences on carbon stocks and ecosystem fluxes (Eller et al, 2020; Flo et al, 2021; Martin et al, 2018; Sabot et al, 2019). Our results indicating that cross‐species interannual growth variability associated with drought is related to WD and hydraulic traits support the importance of such traits on regulating carbon fluxes, which is particularly relevant under the expected increase of drought pressures on forests.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we calculated LC-excess and SW-excess values from a compilation of 112 studies reporting the dual water isotopic composition of plant (stem) and source waters and analysed their relationship with environmental and climatic conditions (air temperature and soil moisture content). In addition, we also assessed the influence of ecologically relevant factors, including mycorrhizal habit and plant functional traits, mediating nutrient and water-use strategies (Chen et al, 2016b;Flo et al, 2021), as well as the comparison 120 between taxonomic groups (angiosperms vs. gymnosperms) with known distinct hydraulic architecture and functioning (Johnson et al, 2012). Our aim was to quantify potential isotopic offsets between plant and source water and their relationship with biotic and abiotic drivers.…”
Section: Introduction 35mentioning
confidence: 99%
“…Previous studies have shown that species with higher g sref tend to show a greater stomatal sensitivity to VPD (Flo et al., 2021; Oren et al., 1999). The results of our FVT models indicated that a similar pattern could exist among genotypes within a species, although this may not hold true for all species (Figure 2).…”
Section: Discussionmentioning
confidence: 95%